Applied features of perforasomes in the revascularization and reconstruction of chronic limb-threatening ischemia in the diabetic foot - Ilayakumar Paramasivam; Balakrishnan Thalaivirithan Margabandu; Poorani Palanisamy; Prethee Martina Christabel; Narayanan Sritharan; Jaganmohan Janardhanan (Indian Journal of Vascular and Endovascular Surgery, 2021)
Chronic limb-threatening ischemia in the diabetic foot is a spectrum disease characterized by the failure of wound healing and increased risk of amputation. The interspecialty consolidating services between the vascular and plastic surgeon with applied perforasome approaches both in the timely revascularization and early reconstruction culminate in the stable and shoeable foot or foot residuum.